2016
DOI: 10.1080/14613808.2016.1189525
|View full text |Cite
|
Sign up to set email alerts
|

Creating bridges: music, play and well-being in the lives of refugee and immigrant children and young people

Abstract: In contemporary society, global population movements, global conflict and ensuing migration have resulted in the presence of bicultural children in many nations, with multiple possibilities for musical engagement emerging within their home and host cultures. For these children, issues of social integration, identity construction, and cultural maintenance and change must be negotiated on a continual basis. This paper explores some of the ways in which music participation, and more specifically, participation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 29 publications
1
37
0
7
Order By: Relevance
“…Initially, the focus was on children's playground singing games, those that are related to an ongoing oral tradition of children's play that has frequently been tapped by music educators seeking repertoire for the classroom (see, for example, Davies, 2005;Jones & Hawes, 1972/87;Kenny, 1975;Lomax, Elder & Lomax Hawes, 1997). From the mid 1980s until the present (following earlier landmark studies, e.g., Blacking, 1967Blacking, /1995, music educators, ethnomusicologists and scholars working in the fields of childhood studies and folklore have undertaken research into children's playground games (Bishop & Curtis, 2001;Burn & Richards, 2014;Campbell, 1991;Countryman, 2014;Emberly, 2013;Gaunt, 2006;Harrop-Allin, 2010;Harwood, 1998aHarwood, , 1998bHarwood & Marsh, 2012;Marsh, 1995Marsh, , 1999Marsh, , 2006Marsh, , 2008Marsh, , 2016Marsh & Bishop, 2014;Marsh & Young, 2016;Merrill-Mirsky, 1988;Minks, 2013aMinks, , 2013bOpie & Opie, 1985/1988Pieridou Skoutella, 2015;Riddell, 1990;Willett, Richards, Marsh, Burn & Bishop, 2013). This research has unpacked the musical and social characteristics of children's playground games and explored the ways in which children teach and learn the games in their own environment.…”
Section: Contexts Of Musical Play In Situmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the focus was on children's playground singing games, those that are related to an ongoing oral tradition of children's play that has frequently been tapped by music educators seeking repertoire for the classroom (see, for example, Davies, 2005;Jones & Hawes, 1972/87;Kenny, 1975;Lomax, Elder & Lomax Hawes, 1997). From the mid 1980s until the present (following earlier landmark studies, e.g., Blacking, 1967Blacking, /1995, music educators, ethnomusicologists and scholars working in the fields of childhood studies and folklore have undertaken research into children's playground games (Bishop & Curtis, 2001;Burn & Richards, 2014;Campbell, 1991;Countryman, 2014;Emberly, 2013;Gaunt, 2006;Harrop-Allin, 2010;Harwood, 1998aHarwood, , 1998bHarwood & Marsh, 2012;Marsh, 1995Marsh, , 1999Marsh, , 2006Marsh, , 2008Marsh, , 2016Marsh & Bishop, 2014;Marsh & Young, 2016;Merrill-Mirsky, 1988;Minks, 2013aMinks, , 2013bOpie & Opie, 1985/1988Pieridou Skoutella, 2015;Riddell, 1990;Willett, Richards, Marsh, Burn & Bishop, 2013). This research has unpacked the musical and social characteristics of children's playground games and explored the ways in which children teach and learn the games in their own environment.…”
Section: Contexts Of Musical Play In Situmentioning
confidence: 99%
“…Music educators working in school and community settings may act as facilitators of music programs that aim to assist young forced and voluntary migrants with managing resettlement processes. However, while such support is undoubtedly necessary and welcome, more recent research has indicated that children and young people who are refugees or voluntary migrants are also agentive social actors, capable of employing strategies that actively help to meet their own emotional and social needs (Hart, 2014) and able to autonomously utilise music for such purposes (Marsh, 2012, 2016, Marsh & Dieckmann, 2016. Musical play provides a particular mechanism by which children can achieve psychosocial adjustment.…”
Section: Global Population Movements and Contexts Of Musical Playmentioning
confidence: 99%
“…However, while such support is undeniably valuable, more recent research indicates that children and young people who are refugees or voluntary migrants also function as agentive social actors, and may consciously employ strategies that assist with meeting their own emotional and social needs (Hart 2014). Recent studies point to the role of music in providing collaborative avenues for enhancing social inclusion, identity construction, and self-expression for young refugees and immigrants Marsh 2012Marsh , 2013Marsh , 2015Marsh , 2017Marsh and Dieckmann 2016).…”
Section: The Bridging Musical Worlds Projectmentioning
confidence: 99%
“…However, while such support is undeniably valuable, more recent research indicates that children and young people who are refugees or voluntary migrants also function as agentive social actors, and may consciously employ strategies that assist with meeting their own emotional and social needs (Hart 2014). Recent studies point to the role of music in providing collaborative avenues for enhancing social inclusion, identity construction, and self-expression for young refugees and immigrants (Karlsen 2013;Marsh 2012Marsh , 2013Marsh , 2015Marsh , 2017Marsh and Dieckmann 2016).…”
Section: The Bridging Musical Worlds Projectmentioning
confidence: 99%